Teologi Perjanjian dalam Perspektif Reformasi: Antara Tradisi dan Pembaruan - Relfan Rolos (ATOHEMA: Jurnal Teologi Pastoral Konseling, 2026)
Covenant Theology is one of the important pillars in Reformation theological thought that seeks to understand the relationship between God and His people through a consistent covenant framework throughout the biblical narrative. This paper examines the development of the concept of Covenant Theology in the Reformation tradition, especially as developed by figures such as John Calvin and post-Reformation theologians, and how this concept has been renewed in dialogue with contemporary theological and social contexts. This study uses a historical-theological and hermeneutic approach to trace the continuity and dynamics of change in the understanding of the covenant, both in the Old and New Testaments. It also emphasizes the contribution of Covenant Theology to the formation of Christian soteriology, ecclesiology, and ethics doctrines within the Reformation framework. The results of the study show that although the traditional roots of Covenant Theology are very strong, there is significant room for theological renewal that remains faithful to Reformation principles such as sola scriptura and sola gratia, without losing the richness of its historical heritage. Thus, Covenant Theology in the Reformation perspective continues to be relevant and dynamic as a bridge between the heritage of faith and the challenges of the modern era.